Feeding Africa: How small-scale irrigation can help farmers to change the game - Bryan, Elizabeth; Ringler, Claudia (The Conversation, 2023)
Unlike large-acreage government irrigation schemes, small-scale irrigation is typically farmer led. Farmers decide what technologies to use to extract water, be it manual lifting or solar water pumps. They also choose the mode of irrigation, whether by buckets or drip kits. Farmers purchase, run and maintain the operation themselves on their own farms or as part of small groups of farmers. Small-scale irrigation can help smallholder farmers to increase agricultural productivity and incomes. It can be scaled quickly and without large public investments. For these reasons, it can contribute more rapidly to the achievement of national agricultural and development goals, compared to large irrigation schemes.